S20-3: Physical Activity Policy Implementation: Development of IMPAQTs List of Best Practice Exemplars (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The ‘IMproving Physical Activity policies and their impact on health eQuiTy’ (IMPAQT) project aims to strengthen physical activity (PA) policymaking across countries by undertaking policy assessment and benchmarking. To enable policy benchmarking, Best Practice Exemplars (BPEs) are required. BPEs are short, informative descriptions not only of physical activity policies themselves, but also include evidence of implementation of the policy in different countries globally. The BPEs map onto the 45 indicators of the PA-EPI (known as Good Practice Statements, or GPSs), a tool that IMPAQT will use to perform policy assessments.Methods: BPE sourcing is undertaken using several complementary methods: searches of scientific literature or policy literature, internet keyword searches, consultation with relevant experts or accessing targeted websites. Identified candidates are then standardised using IMPAQT’s reporting guidelines, with supplementary searches conducted to ensure key implementation details are captured. Reporting guidelines include: fit to the GPS, evidence of equity consideration, evidence of reach or adoption, evidence of sustained budget, and evidence of IMPAQT. Appraisal will be undertaken by the IMPAQT Steering Committee, using an online questionnaire, reducing the number to a final list of BPEs. Finally, candidates are appraised against these guidelines, resulting in a refined list of well-documented physical activity policies.Results: 117 BPE candidates covering all 45 PA-EPI GPSs have been produced by IMPAQT so far. This preliminary list includes BPEs from 27 different countries from across the globe, including examples from both national and subnational levels of government.Conclusions: The list of BPE candidates reflects the variety of policies that have been implemented globally to promote physical activity. It is anticipated that IMPAQTs work in assembling and sharing the list of BPEs will promote policy learning for both researchers and policymakers by showcasing best practice and promoting high standards of policy enactment. These effects are more likely to be realised if mechanisms are put in place to ensure the continuous updating of this best practice database.Support/Funding Source: The IMPAQT project received funding from Ireland, Health Research Board; Poland, National Centre for Research and Development; Germany, Federal Ministry of Education and Research; The Netherlands, The Netherlands Organisation for Health Research and Development; Romania, Executive Agency for Higher Education, Research, Development and Innovation Funding; Lithuania, Research Council of Lithuania, under the umbrella of the Partnership Fostering a European Research Area for Health (ERA4Health) (GA N° 101095426 of the EU Horizon Europe Research and Innovation Programme).Keywords: PA-EPI, benchmarking, policy implementation, international comparison, standardisation